Respon Morfologi dan Fisiologi Bibit Kelapa Sawit dalam Kondisi Tercekam Air terhadap Pemberian Pupuk Biosilika - Eki Rizky Amanta (Fakultas Pertanian, 2025)
Oil palm is one of the most important plantation crops in Indonesia, as it is the largest palm oil producer in the world. The increasing demand for palm oil, including as an energy ingredient for biodiesel, requires an increase in palm oil productivity. One of the strategies to increase oil palm productivity is to provide superior seeds. This study was conducted to determine the morphological and physiological responses of oil palm seedlings under water stress conditions to the application of bio silica fertilizer. Bio silica fertilizer is known to improve plant structure to increase plant resistance from water stress. The addition of PGPR as a biostimulant and helps dissolve silica so that it can spur plant growth. The research was conducted using a factorial Randomized Group Design (RAK) with 2 treatment factors. The first factor is water stress with control level, drought (40%), and inundation (100%) and the second factor is bio silica fertilizer with a treatment level of 30 combinations of water stress treatment and bio silica fertilizer 0 grams/plant, 2.5 grams/plant, 2.5 grams/plant + Rhizomax, 2.5 grams/plant + Floraone, 5 grams/plant, 5 grams/plant + Rhizomax, 5 grams/plant + Floraone, 7.5 grams/plant, 7.5 grams/plant + Rhizomax, and 7.5 grams/plant + Floraone so that 30 treatment combinations were obtained, each repeated twice. The observed variables include stem diameter, leaf thickness, leaf angle, leaf color, stem hardness, stomatal density, total chlorophyll, photosynthetic rate, crown fresh weight, root fresh weight, water content, phenol content, and antioxidant activity. The results showed that the interaction of water stress treatment in control or normal conditions with added bio silica fertilizer 5g/plant + Floraone can increase plant resistance while treatment without bio silica fertilizer showed a decrease in all observation variables. So it can be concluded that the application of bio silica fertilizer can increase the resistance of oil palm under water stress conditions.
Reuploud Repository hasyim Mei 2026 Approved by Teddy
Keywords: oil palm; water stress; bio silica fertilizer